"You stole my work! And you stole it poorly!" Choreography, Copyright, and the Problem of Inexpert Iterations. Issue 1 (April 2021) - Gover, K.E.
Abstract: Dance theorists and legal scholars argue that choreography is by nature ill-suited to the conceptual framework provided by copyright, even as there is widespread agreement that works of dance deserve the legal protection and cultural endorsement that its inclusion represents. I reexamine the factors that are often cited as barriers to choreography's suitability for copyright. I argue that choreography is better suited to the copyright regime than it appears, so long as we recognize that the artistic standard for substantial similarity should be different from the legal standard.